2010
DOI: 10.3311/pp.me.2010-2.01
|View full text |Cite
|
Sign up to set email alerts
|

Hysteretic friction of rubber in tribological tests

Abstract: The goal of this paper is to summarize different investigations of FE modelling of rubber hysteretic friction which was produced in the last 4 years in the KRISTAL project (Knowledgebased Radical Innovation Surfacing for Tribology and Advanced Lubrication, EU Project Reference CT-2005-515837). László PálfiDepartment of Machine and Product Design, BME, H-1111 Budapest, Müe-gyetem rkp. 3., Hungary e-mail: palfi.laszlo@gt3.bme.hu Károly VáradiDepartment of Machine and Product Design, BME, H-1111 Budapest, Müe-gye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It is also possibly due to the shear load resulting from the relative movement of the blocks and the temperature rise due to the hysteresis of these loads. In this case, it was possibly observed that the rubber bush was subjected to hysteresis friction that is caused by the energy dissipation due to internal material damping during the deformation process [1,14]. The deformed part occurs during the sliding of a rubber element across the rough surface.…”
Section: Adnan Malaysian Armoured Vehicle Track Shoementioning
confidence: 99%
“…It is also possibly due to the shear load resulting from the relative movement of the blocks and the temperature rise due to the hysteresis of these loads. In this case, it was possibly observed that the rubber bush was subjected to hysteresis friction that is caused by the energy dissipation due to internal material damping during the deformation process [1,14]. The deformed part occurs during the sliding of a rubber element across the rough surface.…”
Section: Adnan Malaysian Armoured Vehicle Track Shoementioning
confidence: 99%
“…To do so, authors create 2D and 3D models to employ FE method for further analysis. In another work, [55], authors focus on tribological tests to determine hysteretic friction of rubber, whereas experimental and analytical study is presented in [56].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the piston, the viscoelastic piston seal is another research area: Váradi and Pálfi [6] investigated the viscoelastic material properties of an EDPM 75 rubber by experiment and FE simulations. Annavarapu et al [7] examined different finite element methods for frictional sliding, such as the Nitsche and the Lagrange method.…”
Section: Introductionmentioning
confidence: 99%